Hydrogen Sulfide Causes Relaxation in Mouse Bronchial Smooth Muscle - Satoko Kubo; Ichiko Doe; Yuko Kurokawa; Atsufumi Kawabata (Elsevier, 2007)
We investigated the effects of NaHS, a hydrogen sulfide (H2S) donor, on the tension of isolated mouse and guinea-pig bronchial rings. NaHS at 0.01 - 10 mM had no effect on the tone of those preparations without precontraction. When the preparation was precontracted with carbachol, NaHS at 0.1 - 3 mM strongly relaxed the mouse rings, but produced only slight relaxation in the guinea-pig rings. The NaHS-induced relaxation in the mouse bronchus was resistant to inhibitors of ATP-sensitive K+ channels, soluble guanylyl cyclase, cyclooxygenase (COX)-1 or COX-2, and antagonists of tachykinin receptors. Thus, NaHS evokes bronchodilation in mice, suggesting a possible role for H2S in the respiratory system. Keywords:: hydrogen sulfide (H2S), smooth muscle, bronchodilation